(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The paper deals with the bryoflora of coenoses, which are associated with chalk slopes and chalky soil in the valleys of Oskil and Vovcha rivers including an area of “ Dvorichanskyi” National Nature Park, “ Vovchanskyi” and “ Siverskodonetskyi” reserves. The annotated list consists of 2 liverwort species and 80 species and varieties of bryophytes, their localities and abundances are listed. Six species are reported as new to Kharkiv region. Among them Tortella inclinata is recorded for the first time to Left-Bank Graminae-Meadow Steppe of Ukraine and Weissia levieri is included to the Red Data Book of European bryophytes. Taxonomic and ecologic patterns of investigated bryoflora are briefly analyzed. A comparison of studied bryoflora with bryofloras of “ Medobory’ and “ Belohorie” natural reserves is provided.